Carbazole-BODIPY dyads: Synthesis, characterization, photophysical and antimicrobial properties - Gurbuz, Hande Eserci; Gunduz, Ezel Oztuerk; Bat-Ozmatara, Merve; Senocak, Ahmet; Okutan, Elif (Elsevier Science Sa, 2023)
Three new boron dipyrromethene (BODIPY) dyes decorated with carbazole (CB) moieties on the meso and styryl positions of BODIPY core have been synthesized, fully characterized, and subjected to photophysical antimicrobial activity, and cyclic voltammetry studies. The presence of CB units confers unique biological features whereas BODIPY state luminescent molecules thanks to their outstanding photophysical properties. The identities of synthesized compounds (4-6) were confirmed by using 1H, 13C, 11B NMR and mass spectrometry. The structure of the CB-BODIPY (4) was also characterized by means of X-ray diffraction. The photophysical processes including absorption maxima, molar extinction coefficient, fluorescence quantum yields, and fluorescence lifetime were investigated by the methods of steady-state UV-Vis absorption and fluorescence spectroscopy. Mono-and distyryl-derivatives (5 and 6) revealed a substantial conjugation effect manifested by an expected bathochromic shift in absorption and emission spectra relative to 4. The geometries of the molecules were optimized by B3LYP/ 6-311G(d, p) and M06-2X/6-311G(d, p) methods and their structural properties were estimated using time dependent density functional theory (TD-DFT) at the same basis set. The antimicrobial efficacies of the CB-BODIPYs (4-6) were studied against S. aureus (Gram-positive), as well as E. coli (Gramnegative) at various concentrations. Noticeably, the mono-(5) and di-(6) styryl derivatives functionalized with two and three CB units displayed superior antibacterial activity against both E. coli and S. aureus with MIC values of 18.43 and 61.79 & mu;M for 5 and 69.86 and 85.22 & mu;M for 6.
Keywords: Borondipyrromethene; Carbazole; Photophysical; Antibacterial; DFT; Cyclic voltammetry